Proyecto de Inversión para la Implementación de uin Centro de Formación Física y Académica para Jóvenes Bachilleres Aspirantes a Cadetes de las Fuerzas Armadas para la ciudad de Loja - Abad Jiménez, Neydi María (2016)
The project feasibility analysis and feasibility for the creation of a Centre of Physics and academic training for young graduates aspiring to the armed forces in the city of Loja, giving young people the opportunity to train for testing was developed. Definition of company, service, project feasibility, demands, market strategies, location, project engineering, hierarchies, organizational, and financial tools: Also, in the framework of the following topics will be developed. In terms of methodology the methods and techniques necessary for the development of this research was used. They, who helped develop the research properly. Then the results of these markets are detailed: As for the implementation of surveys young students who will run the service, it was determined that the existing effective demand is a 99.67%, its per capita use is once per year for every young person, giving a existing unmet demand of 2,513 to 2,069 academic and physical for the first year, with an indirect competition 8 academic centers and one central physical preparation. Thus, in the technical study an installed capacity of 480 services, of which capacity utilization for the first year is 80%, ie 384 services determined; in 5 organizational study structural and functional organization chart diseñoel, determining the hierarchical levels, functions and activities that must meet Integrates the center. Then in the financial investment of $ 585,925.25 study is determinóuna, the NPV of $ 89,520.06, the same that is acceptable; in relation to cost-benefit (RB / C) the center will earn $ 0.90 cents for every dollar invested, recovering their investment after 4 years, 4 months, 16 days and 19 hours, therefore, the center is sensitive to variations they can give in increased revenues and decreased costs without affecting their financial indices. In conclusion, to implement the investment project of the center of training an investment of $ 585,925.25, it will have a 88% contribution by cosios and 12% of financial credit in the bank will be required National Development at an interest rate of 10%. So, it is recommended to keep an affordable price for the service that customers can access it easily and thus attract new customers, generating utility to each of the shareholders of the center "CENCAP FA CIA. LTDA ".